Wobby #32 : Cozy Cosmos : Volume 8. - Schalk, Marjolein; Cartwright, Andrew; Smout, Bart; de Leijer, Boris (s.l. : Wobby-club)
Contributors Wobby#32 : Arthur Devisscher (BE), Dan Zhu (CN), Joost Pollmann (NL), Koes Staassen (NL), Lale Westvind (US), Līva Kandevica (DE), María Medem (ES), Noa Zuidervaart (NL), Rania Esstafa (FR), Robert Schuit (NL), Sander Ettema (NL)
boek